Identification of the factors influencing the liquid sloshing wave height in a sloped bottom tank under horizontal excitation using PCA approach - Ren, Wenhao; Zhong, Zuowei (Frontiers in Built Environment, 2024)
The dynamic behavior of liquid storage tanks represents a pivotal research area concerning structural safety and reliability. Notably, sloped bottom tanks exhibit heightened sloshing with reduced liquid mass compared to rectangular counterparts. This study adopts a hybrid approach that seamlessly integrates the linear potential-flow theory, renowned for its analytical rigor in fluid dynamics modeling, with principal component analysis (PCA), a potent technique for dimensionality reduction and feature extraction. The hybrid methodology initially employs the linear potential-flow theory to simulate the fundamental fluid dynamics within sloped bottom tanks subjected to horizontal excitation. Subsequently, PCA is applied to the simulated data, identifying key components of liquid sloshing wave height variations. Through the analysis of these principal components, an accurate model of the maximum sloshing wave height is derived, achieving a close correlation with ANSYS simulation results, exhibiting a correlation coefficient of 0.98 and a mean absolute error of 2.5%. This approach uniquely facilitates the evaluation of the intricate interplay between multiple factors, including tank geometry and excitation frequency, on the dynamic characteristics of liquid sloshing waves in sloped bottom tanks. The findings emphasize the significant influence of tank height and tilt angle, with a sensitivity analysis indicating a 4.07% increase in maximum wave height per degree increase in tilt angle under specified experimental conditions. This comprehensive methodology not only enhances understanding of the complex liquid sloshing phenomenon but also provides precise theoretical and practical guidance for fluid sway control strategies. Future investigations will further expand the scope and elucidate the fundamental mechanisms governing liquid sloshing dynamics.